2008
DOI: 10.1007/s10552-008-9152-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of body mass index on prognosis in gynecological malignancies

Abstract: Although obesity increases the incidence of cancer, a high BMI does not seem to adversely influence the prognosis in patients with the mentioned gynecological malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 36 publications
(40 reference statements)
4
66
4
Order By: Relevance
“…Three observational cohorts (31,33,34) and the 3 treatment cohorts (9, 24, 25) did not report HRs and so were not included in our initial meta-analysis. All of these studies reported that survival time did not differ significantly between BMI strata, with the exception of the study by Munstedt and colleagues, which found a trend toward improved survival in women who were obese (31).…”
Section: Systematic Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Three observational cohorts (31,33,34) and the 3 treatment cohorts (9, 24, 25) did not report HRs and so were not included in our initial meta-analysis. All of these studies reported that survival time did not differ significantly between BMI strata, with the exception of the study by Munstedt and colleagues, which found a trend toward improved survival in women who were obese (31).…”
Section: Systematic Reviewmentioning
confidence: 99%
“…All of these studies reported that survival time did not differ significantly between BMI strata, with the exception of the study by Munstedt and colleagues, which found a trend toward improved survival in women who were obese (31). Estimates for 2 of these studies (25,31) were, however, included in the previous meta-analysis (8), thus we conducted a sensitivity analysis including this additional information.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…The association between obesity and the prognosis of endometrial cancer remains controversial. Previous studies have suggested that obesity is associated with a worse prognosis, while there no relationship seen in other studies (10)(11)(12)(13) that a high BMI was not associated with the patient survival outcome, but showed a lower recurrence although not of statistical significance. This is probably because an increasing BMI shows a lower FIGO stage, a higher proportion of well-differentiated endometrioid type tumors, and a lower risk factor for recurrence such as lymph node/ovarian metastasis, as well as positive cytology as defined by Keys et al in GOG 99 (14,40).…”
Section: Discussionmentioning
confidence: 77%
“…However, the influence of a high BMI on the prognosis of endometrial carcinoma remains controversial. Obesity has been associated with a worse prognosis of endometrial carcinoma in several published studies, although there was no association in other and in Korean population studies (10)(11)(12)(13)(14). Obesity was once a contraindication for advanced laparoscopic procedures (15,16), although this has recently been reconsidered (17).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from this, studies have shown an inverse relationship between body mass index (BMI) and tumour biology/ grading [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%